1993
DOI: 10.21236/ada273690
|View full text |Cite
|
Sign up to set email alerts
|

Software Inspection Insertion Efforts for the Ballistic Missile Defense Organization

Abstract: IDA Le it,. N UNo" DEFINMTONS IDA peblis hes be elowiu docMUmet to report Oe recaul af its Work. Reports Reports wre the most aubaltnratlve mod mast carefully considered products IDA publishes. They marmaly embody resilla ot major proejcts which (a) kav a direct hearing en declisios affecting mawo ptograms, (b) address Ismus af significant concern to the Executive Breach, IM Congress and/or the public, or IQ) address issues that hae" "signfiant ecanemic Implications. IDA Raperts are reviewed by outside panels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The detection rate for an inspection varies depending on the type of work product being inspected and the specific inspection process used. Studies have found that 30 to 90 percent of the defects in a work product may be uncovered through the inspection process [5].…”
Section: Literature Review 21 Software Inspectionmentioning
confidence: 99%
“…The detection rate for an inspection varies depending on the type of work product being inspected and the specific inspection process used. Studies have found that 30 to 90 percent of the defects in a work product may be uncovered through the inspection process [5].…”
Section: Literature Review 21 Software Inspectionmentioning
confidence: 99%